Impact of SCSP Demonstrations on Good Agricultural Practices in Rice Cultivation - Nirmala, B.; Rathod, Santosha; Sriramulu, T.; Muthuraman, P. (Chronicle of Bioresource Management, 2023)
Rice is the staple food crop of India. A total of 3,284 demonstrations on ‘Good Agricultural Practices’ were organized in five different states of India during 2020-21 under the Scheduled Caste Sub Plan of the Indian Institute of Rice Research. In Telangana and Andhra Pradesh, 2,832 demonstrations were organized. The technology demonstrated included quality seed, herbicide, water pipes and vermicomposting. Also, skill training programs have been organized on various aspects of rice production technology. Drying sheets and sprayers were distributed to the selected SC farmers. The impact of the demonstrations was analysed. The results revealed that the productivity of rice under demonstrations was superior over the control plots in both states. Hence, efforts should be made to promote the adoption of good agricultural practices for enhancing the income of rice farmers.